Three great Kansas forage crops-- alfalfa, corn, and kafir-corn - Scott, John M. (My University, 1907)
Introduction: In treating this subject we will only consider the feeding value of the fodder of these crops, and will not consider the feeding value of the grain, but will compare the feeding value of each as compared with the cost of production and in this way will show which is the most profitable crop for the stockman to feed, also for the farmer to produce. ALFALFA: - Description: Alfalfa is an upright branching smooth perenial plant, growing from one to three feet high, according to conditions. When in bloom it presents a purple or violet color, the flowers instead of being in a head like clover, are in a long,loose cluster or raceme. These are scattered over the plant. The ripe pods are spirally twisted through two or three complete curves, and each pod contains several seeds. Compared with clover it yields heavier. History:- Alfalfa or Lucerne has been cultivated for ages, it was familiar even with the Egyptians, Medes, and Persians. It is said to have grown spontaneously on the high desert regions of Southern and central Asia. It became known in Greece about the time Xerxes invaded that country or about 450 B. C. and was prominent in Roman agriculture before the Christian era. The Romans valued it very highly as forage for the horses of their armies. It was introduced into Spain and southern France from Italy and was carried to Mexico during the Spanish invasion. It was brought from Chili to California in 1854, it soon spread eastward and is now in nearly all of the western states. It is said to have been introduced into New York in 1820 but did not seem to have been valued very highly. Varieties: Besides the common variety, Medicago Saliva, that we are acquainted with here in Kansas. There are two other varieties, they are the…
Citation: Scott, John M. Three great Kansas forage crops-- alfalfa, corn, and kafir-corn. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Kansas Crops; Alfalfa; Corn; Kafir-Corn; Feeding Value; Crop Profitability; Theses